Urban design in the Arab World : reconceptualizing boundaries - Saliba, Robert (England : Ashgate, 2015)
'Most urban designers are familiar with the historical architecture of Islam and its current contribution to postmodernity, particularly in the United Arab Emirates. Less well known however is the singular contribution it has made to urban design. This text contributes a new dimension to our understanding of urban space and form and its links to globalisation, regionalism, culture, and religion. It brings together unique expertise to reveal the much neglected complexity of urbanism in the Arab world.' Alexander Cuthbert, The University of New South Wales, Australia'The Arab City, a post-Islamic city concept, is the prism through which this collection of essays examines both the practice of urban design and the various discursive frameworks shaping it today. Deftly deploying critical, poststructuralist, and postcolonial theories, the book manages to pose fundamental questions about the status of urbanism, design, and politics before and after the Arab Spring.' Nasser Rabbat, Massachusetts Institute of Technology, USA -- Publisher Synopsis.
Contents: Framing urban design on the margins: global paradigms and regional implications, Robert Saliba; Medina - the'Islamic','Arab','Middle Eastern' city: reflections on an urban concept, Nezar AlSayyad. Part I The Discursive: Reconceptualizing Boundaries between the Diverse and the Conflictive: The cultural discourse: on regionalism in urban design and the role of the Aga Khan Award for Architecture, Omar Abdulaziz Hallaj; The participative discourse: community activism in post-war reconstruction, Howayda Al-Harithy; The corporate discourse: learning from Beirut's central area renewal, Angus Gavin; The greening discourse: ecological landscape design and city regions in the Mashreq, Jala Makhzoumi. Part II The Hybrid: Blurring Boundaries between Design Disciplines: Cultural infrastructure for the margins: a machinic approach to Nahr Beirut, Lee Frederix; Architectural urbanism: proposals for the Arab world, Sam Jacoby. Part III The Operational: Bridging Boundaries between Research and Practice: Aleppo 2025 City Development Strategy: a critical reflection, Ali Saad and Thomas Stellmach; Community-based design as mediator between academia and practice: the case of Souq Sabra, Beirut, Rabih Shibli; [Trans]forming Nahr Beirut: from obsolete infrastructure to infrastructural landscape, Sandra Frem. Part IV The Visionary: Crossing Boundaries between the Utopian and the Real: Sites of globalization: new cities - reflecting on the dialectics between designer and client, Anne Marie Galmstrup; Sites of worship: from Makkah to Karbala - reconciling pilgrimage, speculation and infrastructure, Robert Saliba; Sites of conflict: Baghdad's suspended modernities versus a fragmented reality, Caecilia Pieri; Sites of contestation: Tahrir Square - from appropriation to design, Robert Saliba, Hussam Hussein Salama and Nathan Cherry. Part V Prospects: Future Urban Design Agendas: Estidama as a model for sustainable urbanism in the Arab world: the case study of Abu Dhabi, John Madden; Re-engineering the twenty-first-century city: future directions for urban design in the Arab world, Anne Vernez Moudon. Index.
Includes bibliographical references and index.
Keywords: City planning -- Arab countries; Urbanization -- Arab countries